Functional gastrointestinal disorders in adolescents during online learning - Simanjuntak, Sumardi F.; Prawitasari, Titis; Kadim, Muzal; Sari, Teny Tjitra; Gunardi, Hartono; Vandenplas, Yvan; Hegar, Badriul (Paediatrica Indonesiana, 2023)
Background The COVID-19 pandemic necessitated the use of online schooling in order to comply with national and local lockdown guidelines. Online learning required students and teachers to adapt to a new method of schooling. The inability of adolescents to adapt to their environment can interfere with their psychosocial condition and become a risk factor for functional gastrointestinal disorders (FGID). Objective To determine the prevalence of FGID in adolescents and evaluate possible risk factors that existed during online learning. Methods This cross-sectional study was done in children aged 12-18 years who participated in online learning during the COVID-19 pandemic. The diagnosis of FGID was based on Rome IV criteria. Psychosocial problems were assessed using the Pediatric Symptom Checklist Questionnaire–17 (PSC-17) which includes internalization, externalization, and attention subscales. Subjects with a PSC-17 mixed subscale total score of >15 were considered as having an increased likelihood of having a behavioral health disorder. Data were collected by online questionnaires via Google Forms. Results Of 1,413 participants, 23% experienced FGID; of these, 32.6% had >2 FGID diagnostic criteria. Upon multivariate analysis, internalization psychosocial problems were the most common risk factors for FGID, followed by mixed subscale psychosocial problems, unstable internet connection, and not understanding of the material. ConclusionThe prevalence of FGID in adolescents in this study is 23%. Environmental and psychosocial conditions are interrelated as risk factors for FGID in adolescents during online learning in the COVID-19 pandemic.